Publisher Correction to: A review of advances in resistance spot welding of automotive sheet steels: emerging methods to improve joint mechanical performance (The International Journal of Advanced Manufacturing Technology, (2022), 118, 5-6, (1335-1366), 10.1007/s00170-021-08002-5) - Soomro, I.A. (Springer Science and Business Media Deutschland GmbH, 2022)
Due to an error in typesetting the original publication of âA review of advances in resistance spot welding of automotive sheet steels: emerging methods to improve joint mechanical performanceâ contained the same images of Figs. 14 and 15. The correct image of Fig. 15 is now shown below: Â© Springer-Verlag London Ltd., part of Springer Nature 2022.